High temperature fatigue tests and crack growth in 40CrMoV13.9 notched components - P. Gallo; F. Berto (Fracture and Structural Integrity)
The present paper addresses experimentally the high temperature fatigue of 40CrMoV13.9 steel and the effect of surface roughness on fatigue strength and crack initiation. The 40CrMoV13.9 steel is widely used in different engineering high temperature applications among which hotrolling of metals, where, in order to assure a constant temperature, the rolls are provided with cooling channels. These are the most stressed zone of the rolls where cracks systematically initiate. In order to completely characterize the high temperature behaviour of this steel, firstly uniaxial-tension load controlled fatigue tests have been conducted at different temperatures up to 650°C. Two geometries are considered: plain specimens and plates weakened by symmetric V-notches. Subsequently, with the aim to investigate the influence of the cooling channels roughness on the high temperature behaviour and the cracks initiation, uniaxial-tension load controlled fatigue tests have been conducted on plate with central hole at the service temperature of 650°C varying the surface roughness. After a brief review of the recent literature, the experimental procedure is described in detail and the new data from un-notched and notched specimens are summarized in terms of stress range, at the considered temperatures. Finally, fatigue data from un-notched and notched specimens are re-analysed by means of the mean value of the Strain Energy Density (SED) approach extended at high temperature.